Peramalan Cuaca Harian di Kota Purwokerto Menggunakan Metode Rantai Markov - Sausan; Ernawati Prahesta Kurnia Sari; Abdurrahman Muhammad Umar Lahmadi (Mathematics Study Program, Faculty of Mathematics and Natural Science, Universitas Negeri Jakarta, 2024)
Daily weather forecasting is an important aspect in anticipating and managing the impact of weather changes that can affect various sectors of life, such as agriculture, transportation, tourism, and other activities. Purwokerto City, which is located in the middle of Java Island, Indonesia, is one of the cities that faces fluctuating weather changes. This research aims to perform daily weather forecasting in Purwokerto City using the Markov Chain Method, a statistical approach that has been widely used in various fields including weather forecasting. This research uses daily weather data in Purwokerto City on July 5 to 10, 2023. The data was obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG) Purwokerto City. The weather data is based on the weather categories of cloudy, light rain, moderate rain, and thunder rain, as well as observation time which includes morning, afternoon, evening, and night. The results showed that the daily weather data from July 5 to 10, 2023 analyzed showed significant weather variations. However, cloudy weather was the most dominant condition during that week.